Phase I dose escalation study of concurrent palliative radiation therapy with sorafenib in three anatomical cohorts (Thorax, Abdomen, Pelvis): The TAP study. Issue 1 (July 2017) - Murray, Louise; Longo, Joseph; Wan, Jonathan; Chung, Caroline; Wang, Lisa; Dawson, Laura; Milosevic, Michael; Oza, Amit; Brade, Anthony
Abstract: Background and purpose: To evaluate the tolerability and maximum tolerated dose (MTD) of sorafenib administered concurrently with palliative radiotherapy. Material and methods: In patients with incurable cancer, sorafenib was escalated independently in three cohorts based on irradiation site: thorax, abdomen or pelvis. Sorafenib was administered days 1–28 and radiotherapy (30 Gy in 10 fractions) was delivered days 8–12 and 15–19. Dose-limiting toxicities (DLT) were acute grade 3+ toxicities attributable to radiotherapy. Results: For the thorax, abdomen and pelvis cohorts, 14, 16 and 4 patients were recruited, and Dose Levels 3, 3 and 2 were reached, respectively. Sorafenib-related systemic toxicity led to significant sorafenib interruption in 10 patients. There were 3 DLTs in total, one per cohort: grade 3 oesophagitis (thoracic), transaminase elevation (abdominal) and grade 5 bowel perforation (pelvic; patient with tumour invading bowel). Grade 2 radiation dermatitis developed in 12 patients. The trial was terminated early as slow accrual and sorafenib-related systemic toxicity prevented efficient evaluation of RT-related DLTs. Conclusions: The MTD of sorafenib when used with 30 Gy in 10 fractions was not established due to sorafenib-related systemic toxicity. Severe radiotherapy-related toxicities were also observed. These events suggest this concurrent combination does not warrant further study.